Produksi Asam Laktat dan Pola Pertumbuhan Bakteri Asam Laktat dengan Pemberian Dosis Rendah Propolis Trigona spp asal Pandeglang Indonesia - Akhmad Endang Zainal Hasan; I Made Artika; Syaeful Abidin (Current Biochemistry, 2014)
Propolis is known to have an antimicrobial activity and can prevent various diseases. Propolis consumption is feared to have negative impact on the activity of digestive lactid acid bacteria (LAB). The aim of this research was to examine the effect of propolis on the growth and lactic acid production of three LAB. Ethanol Extraction Propolis (EEP) concentrations examined were control, eep and X propolis 0% (control), 0.2%, 0.6%, 1.0% and X propolis at 0.4% concentration. The parameters analyzed were the growth of bacteria counted with Total Plate Count (TPC) method and lactic acid production using titrable acidity analysis. Propolis at 0,6% concentration stimulated the growth of Lactobacillus casei subsp. rhamnosus (LCR, 24.725x108 cell/mL), but inhibited the average lactic acid production (0.071%) lower than control (0,149%). Propolis did not affect the growth of Streptococcus thermophillus (STP), but propolis at 0,6% concentration stimulated lactic acid production (0.182%) higher than control (0.112%). Propolis inhibited the growth of Lactobacillus delbrueckii subsp. bulgaricus (LDB), but at 0,2% concentration, its population was still highest (3.775x108 cell/mL) and lactic acid production was stimulated (0.195%) higher than control (0.123%).